2013
DOI: 10.1097/moo.0b013e3283658eb0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cough

Abstract: Purpose of review The purpose of this review is to highlight recent work and provide recommendations on the approach for diagnosis and management of chronic cough in a gastroenterology clinic. Recent findings Chronic cough is a burdensome symptom affecting a large number of patients and contributes significant cost to the healthcare system. Recent work has shown that select patients may benefit from acid suppressive therapy and even surgery when there is true pathologic evidence of reflux disease with cough.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Consequently, lung diseases often coexist with intestinal disorders or combined lung‐intestinal conditions, providing a modern theoretical basis for the application of lung‐intestine combined treatment. Previous studies have indicated that apart from respiratory symptoms, mice with pulmonary inflammation also exhibit digestive symptoms like constipation 27 . This study found that PIC mice not only have respiratory inflammation but also have pathological changes in the colon tissue, including destruction of the colon mucosal epithelium, shallow crypt structures, and mild infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Consequently, lung diseases often coexist with intestinal disorders or combined lung‐intestinal conditions, providing a modern theoretical basis for the application of lung‐intestine combined treatment. Previous studies have indicated that apart from respiratory symptoms, mice with pulmonary inflammation also exhibit digestive symptoms like constipation 27 . This study found that PIC mice not only have respiratory inflammation but also have pathological changes in the colon tissue, including destruction of the colon mucosal epithelium, shallow crypt structures, and mild infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have indicated that apart from respiratory symptoms, mice with pulmonary inflammation also exhibit digestive symptoms like constipation. 27 This study found that PIC mice not only have respiratory inflammation but also have pathological changes in the colon tissue, including destruction of the colon mucosal epithelium, shallow crypt structures, and mild infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 67%
“…If the cough does not improve, PPI treatment should be stopped. 56 Physiological testing should be reserved for refractory patients with strong clinical suspicion or being considered for anti-reflux surgery. 57 In refractory cases after a short trial of PPI, an ambulatory reflux monitoring by 24 h esophageal pH and impedance monitoring can be performed off PPI treatment in order to confirm GORD diagnosis and limit empirical use of GORD treatment.…”
Section: Frequent Causes Of Chronic Coughmentioning
confidence: 99%
“… 57 In refractory cases after a short trial of PPI, an ambulatory reflux monitoring by 24 h esophageal pH and impedance monitoring can be performed off PPI treatment in order to confirm GORD diagnosis and limit empirical use of GORD treatment. 56 This technique can detect episodes of both liquid and aerosolized acid (pH<4), mildly acid (pH 4–7) and alkaline (pH>7) reflux. 11 Different biomarkers for reflux associated cough have been studied, including pepsin and lipid-laden alveolar macrophages in broncho-alveolar lavage.…”
Section: Frequent Causes Of Chronic Coughmentioning
confidence: 99%
“…They paid more attention to the objective tests [ 4 , 5 ]. However, the problem is the low availability, poor efficacy, and high cost of some major diagnostic tests [ 6 - 12 ] in developing countries, such as in China. In addition, in case of patients for whom a specific etiology of chronic cough is not apparent, ACCP guideline said empiric therapy for UACS in the form of a first-generation A/D preparation should be prescribed before beginning an extensive diagnostic workup [ 13 ].…”
Section: Introductionmentioning
confidence: 99%